Strategies to capture biotechnology opportunities in Chile - Cuevas,Cristian Hernandez (Pontificia Universidad Católica de Valparaíso, 2004)
Two complementary strategies are proposed to help develop the biotechnology industry in Chile. The objectives of such propositions are based on identifying business opportunities, which can be transformed into biotechnology projects that complement the competitive advantages of the most active areas of the Chilean economy. As a result, the establishment of these initiatives may create the proper business environment where good information, investors’ safeguards and economic incentives would be provided to encourage investors to support new biotechnology ventures focused on mining, aquaculture, forestry, as well as wine and fruit production. In addition, a complete description of the Chilean biotechnology industry is provided. Amongst other characteristics, this report shows that the industry lacks financial support from venture capital and foreign investors, has a relatively modest proportion of highly qualified employees that work in Research and Development, presents insufficient patent productivity and is mostly regulated in terms of the use of GMOs.